EFEKTIVITAS PEMBERIAN DUKUNGAN DAN APRESIASI PADA SISWA DALAM PEMBELAJARAN MATEMATIKA DI SMK NEGERI 1 SINUNUKAN - Siska Yanti; Roslian Lubis; Marzuki Ahmad (JURNAL MathEdu (Mathematic Education Journal), 2022)
Abstract This study aims to describe the ability to learn mathematics before being given support and appreciation in class X SMK Negeri 1 Sinunukan. Knowing the support and appreciation of students for learning mathematics in class X SMK Negeri 1 Sinunukan. This research was conducted at SMK Negeri 1 Sinunukan. The research method used is an experimental method using a one group pretest design, namely one type of treatment. The population of this class is all students of class X TO 1 SMK Negeri 1 Sinunukan which consists of one class that collects 23 students. The sample of this research is class X TO 1 as many as 23 students. Data collection techniques used are observation and tests. The data collected were analyzed in two stages, namely descriptive analysis and inferential analysis. Based on the research, it is known that the provision of support in class X TO 1 of SMK Negeri 1 Sinunukan from the results of observations made in the very good category with an average value of 4.10. The description of the provision of support in class X TO 1 of SMK Negeri 1 Sinunukan from the observations made is known to be in the good category with an average score of 4.00. Then the description of student learning after using the provision of support and appreciation with an average score of 86.09 with a very good category. results Based on the hypothesis test conducted, the value of Sig. (2-tailed) of 0.000 known probability value of 0.005 with the keyword Sig (2-tailed) of 0.000 < 0.005. Based on the value consultation, the alternative hypothesis is accepted or approved for truth. “Providing effective support and appreciation to improve mathematics learning at SMK Negeri 1 Sinunukan. Then the percentage of classical completeness data is 73.91% with the effective category. Then the N-Gain value is obtained as 1.56, which is a very high classification. Keywords: Support and Appreciation, Mathematics Learning, Students.